Icaritin Sensitizes Thrombin- and TxA2-Induced Platelet Activation and Promotes Hemostasis via Enhancing PLCγ2-PKC Signaling Pathways - Zhu, Zhixiang; Luo, Yanggan; Liao, Hanjing; Guo, Ran; Hao, Doudou; Lu, Zihan; Huang, Manjing; Sun, Chenghong; Yao, Jingchun; Wei, Ning; Zeng, Kewu; Tu, Pengfei; Zhang, Guimin (Thrombosis and Haemostasis, 2024)
Background Vascular injury results in uncontrollable hemorrhage in hemorrhagic diseases and excessive antithrombotic therapy. Safe and efficient hemostatic agents which can be orally administered are urgently needed. Platelets play indispensable roles in hemostasis, but there is no drug exerting hemostatic effects through enhancing platelet function.Methods The regulatory effects of icaritin, a natural compound isolated from Herba Epimedii, on the dense granule release, thromboxane A2 (TxA2) synthesis, α-granule release, activation of integrin αIIbβ3, and aggregation of platelets induced by multiple agonists were investigated. The effects of icaritin on tail vein bleeding times of warfarin-treated mice were also evaluated. Furthermore, we investigated the underlying mechanisms by which icaritin exerted its pharmacological effects.Results Icaritin alone did not activate platelets, but significantly potentiated the dense granule release, α-granule release, activation of integrin αIIbβ3, and aggregation of platelets induced by thrombin and U46619. Icaritin also shortened tail vein bleeding times of mice treated with warfarin. In addition, phosphorylated proteome analysis, immunoblotting analysis, and pharmacological research revealed that icaritin sensitized the activation of phospholipase Cγ2 (PLCγ2)-protein kinase C (PKC) signaling pathways, which play important roles in platelet activation.Conclusion Icaritin can sensitize platelet activation induced by thrombin and TxA2 through enhancing the activation of PLCγ2-PKC signaling pathways and promote hemostasis, and has potential to be developed into a novel orally deliverable therapeutic agent for hemorrhages.
Keywords: icaritin; sensitizing effects; platelet activation; hemostasis; phospholipase Cγ2; protein kinase C